Evaluasi Media Promosi Kesehatan Jiwa Mengenai Pencegahan Kekambuhan Dan Penanganan Pasien Pasca Pasung Di Sukoharjo - Palupi, Widya Meiilina; Widodo, Arif (Universitas Muhammadiyah Surakarta, 2020)
Poster is one of the media that can help kelurga in improving knowledge of the care of souls including patients after pasung. to prevent a recurrencePosters appropriate acceptable by the readers when system making posters easily learned that the purpose and objective. can be achievedThe purpose of this research to know the media on the prevention of mental health patients after a recurrence and handling pasung in sukoharjo. A method of the research uses descriptive qualitative .Design from the study adopting phenomenology .Participants research was 6 cadres health and 6 family members .Instrument the research uses posters as a medium evaluation. Analysis data using data central tendency and open question about evaluation posters.The research results show most of family about posters agree about the matter, language, the design, and materials on posters as a medium cadres and promotion of health soul by family on a recurrence and handling the patients after pasung. Most of the family having given promotion on the mental health patients after a recurrence and handling pasung said there are part of poster still is there is a shortage, as the activity treatment and give advice repaired posters in matter. 1